THE INFLUENCE OF CLIMATE CHANGE ON SUNFLOWER YIELD IN THE NORTHERN STEPPE OF UKRAINE: ANALYSIS AND FORECAST - Zhygailo, О. L.; Volvach, O. V.; Tolmachova, А. V.; Kostiukievych, T. K. (Scientific Progress & Innovations, 2021)
Global climate changes are creating new conditions for all sectors of the world and Ukrainian economy, including agriculture. Their influence is associated with agro-climatic conditions for growing crops, including sunflower. The assessment of these conditions is relevant because they must be taken into account in the potential adaptation of sunflower to climate change and the profitability of its cultivation in certain natural climatic zones of Ukraine. The aim of this study was to identify the degree of climate change influence on sunflower yield. Modern RCP2.6 and RCP4.5 scenarios (moderate and medium greenhouse gas emissions) were used to assess the impact of climate change on sunflower yields. According to these scenarios, the climatic period from 2021 to 2050 was studied. For the comparative analysis of scenario meteorological values with the previous data, the period from 1980 to 2010 was taken. The study of sunflower yield formation was carried out using a mathematical model for estimating agro-climatic resources of crop productivity formation, adapted for sunflower cultivation. According to the calculations, an increase in PAR (by 8 and 21 %) in both scenarios will lead to an increase in the potential sunflower yield (up to 1.63 t/ha and 1.83 t/ha against 1.51 t/ha). According to the RCP2.6 scenario, agro-climatic conditions (increased temperature (by 0.7 ºC) and sufficient precipitation for drought-resistant sunflower, 223 mm) will increase the photosynthetic potential, and a slight increase in MPU (0.83 t/ha vs. 0.81 t/ha). Some increase in seed yield (by 4 %) is expected. Agro-climatic conditions under the RCP4.5 scenario will be drier during the flowering-ripening period. But sunflower yield will not be significantly affected by these conditions. Seed yield is expected to be the same as under the actual average long-term conditions (2.3 t/ha). Under the implementation of both scenarios due to the positive impact of expected climatic conditions on all categories of sunflower yields in the next three decades, sunflower will be one of the most popular and profitable crops in the Northern Steppe of Ukraine.